Exposure to phenanthrene and depuration: Changes on gene transcription, enzymatic activity and lipid peroxidation in gill of scallops Nodipecten nodosus - Piazza, Romi S.; Trevisan, Rafael; Flores-Nunes, Fabricio; Toledo-Silva, Guilherme; Wendt, Nestor; Mattos, Jaco J.; Lima, Daina; Taniguchi, Satie; Sasaki, Silvio Tarou; Mello, Alvaro C. P.; Zacchi, Flavia L.; Serrano, Miguel A. S.; et al. (Elsevier B.V., 2016)
Understanding the mechanism of phenanthrene (PHE) biotransformation and related cellular responses in bivalves can be an important tool to elucidate the risks of polycyclic aromatic hydrocarbons (PAHs) to aquatic organisms. In the present study it was analyzed the transcriptional levels of 13 biotransformation genes related to cytochrome P450 (CYP), glutathione S-transferase (GST), sulfotransferase (SULT), flavin-containing monooxygenase and fatty acid-binding proteins by qPCR in gill of scallops Nodipecten nodosus exposed for 24 or 96 h to 50 or 200 mu g L-1 PHE (equivalent to 0.28 and 1.12 mu M, respectively), followed by depuration in clean water for 96 h (DEP). Likewise, it was quantified the activity of catalase (CAT), glutathione peroxidase (GPx), superoxide dismutase (SOD), glutathione reductase (GR), glucose 6 phosphate dehydrogenase (G6PDH), GST and levels of lipid peroxidation. Increased transcriptional levels of CYP2U1-like, CYP2D20-like, CYP3A11-like, GSTomega-like, SULTIBI-like genes were detected in organisms exposed to PHE for 24 or 96 h. In parallel, GR and GPX activities increased after 96 h exposure to 200 mu g L-1 PHE and G6PDH activity increased after 24 h exposure to 50 mu g L-1 PHE. This enhancement of antioxidant and phase I and II biotransformation systems may be related to the 2.7 and 12.5 fold increases in PHE bioaccumulation after 96 h exposure to 50 and 200 mu g L-1 PHE, respectively. Interestingly, DEP caused reestablishment of GPX and GR activity, as well as to the transcript levels of all upregulated biotransformation genes (except for SULTIBI-like). Bioaccumulated PHE levels decreased 2.5-2.9 fold after depuration, although some biochemical and molecular modifications were still present. Lipid peroxidation levels remained lower in animals exposed to 200 mu g L-1 PHE for 24 h and DEP. These data indicate that N. nodosus is able to induce an antioxidant and biotransformation-related response to PHE exposure, counteracting its toxicity, and DEP can be an effective protocol for bivalve depuration after PHE exposure. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Phenanthrene; Biotransformation; Scallops; Nodipecten nodosus; Depuration; Mollusks